Adidas AG : equity valuation - Seeger, Tom Lukas (2019)
This thesis aims to present a sophisticated valuation for the Adidas Group at the 7th of January 2019. The analyzed company is an internationally operating firm of the sports & apparel sector, based in Herzogenaurach in Germany and is a component of Germany´s blue chip index DAX30. To provide a final evaluation about the current share price of Adidas, two different valuation approaches were performed. The discounted cash-flow analysis reflects the essential part of this dissertation and was backed up by a peer group multiple analysis. After deriving equity values in both approaches, main assumptions were compared with an equity research recommendation of the German private bank Hauck & Aufhäuser, published in July 2018. Finally, after considering all created models and the underlying assumptions, a BUY recommendation was expressed for Adidas since most of the computed results vary above the current share price. Especially the implication of the DCF result gives occasion to believe in a further growth potential of the Adidas stock.